Psychology : a very short introduction - Butler, Gillian; McManus, Freda (New York : Oxford University Press, 2000)
A short introduction to psychology, explaining what it is and how it should be studied, and discussing perception, learning and memory, thinking, reasoning and communicating, motivation and emotion, individual differences, and other related topics.
Includes bibliographical references (p. 151-153) and index.
Adult
Keywords: Psychology; Psychology